2019
DOI: 10.1103/physrevb.99.174403
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and entanglement after a geometric quench in the XXZ chain

Abstract: We investigate the dynamics of the XXZ spin chain after a geometric quench, which is realized by connecting two half-chains prepared in their ground states with zero and maximum magnetizations, respectively. The profiles of magnetization after the subsequent time evolution are studied numerically by density-matrix renormalization group methods, and a comparison to the predictions of generalized hydrodynamics yields a very good agreement. We also calculate the profiles of entanglement entropy and propose an ans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…Consequently, the entanglement properties in the dynamical and static problems are identical. The entanglement entropy for a biased hopping chain was studied in [55,[57][58][59] between two parts of the chain, with the cut located somewhere along the emerging front. The growth was found to be logarithmic, however with a different prefactor as for the local (unbiased) quench.…”
Section: A Homogeneous Chainmentioning
confidence: 99%
“…Consequently, the entanglement properties in the dynamical and static problems are identical. The entanglement entropy for a biased hopping chain was studied in [55,[57][58][59] between two parts of the chain, with the cut located somewhere along the emerging front. The growth was found to be logarithmic, however with a different prefactor as for the local (unbiased) quench.…”
Section: A Homogeneous Chainmentioning
confidence: 99%
“…Letting the system evolve, the domain wall starts to melt, giving rise to an expanding front region characterized by a nonzero spin current. The resulting magnetization profiles were studied in various integrable spin models such as the XX chain [6][7][8], the transverse Ising (TI) [9][10][11], the XY [12] as well as the XXZ chains [4,[13][14][15][16][17]. Rather generically one finds ballistic transport, with the exception of the isotropic Heisenberg chain where a diffusive behaviour is observed instead [18][19][20][21][22].…”
mentioning
confidence: 99%
“…Halfway between these two scenarios, a peculiar class of quantum quenches is that of bi-partitioning protocols see e.g. [9-11, 13, 30, 37, 64-71], where a logarithmic growth of entanglement [30,37,64,65,67] is associated with the integrability of the model. In this context, a remarkable example is the time-evolution of a domain-wall state |↑ .…”
Section: Introductionmentioning
confidence: 99%
“…↓ (in some literature this protocol is known as a geometric quench [65,67,72]). This setup has been studied intensively in the past and the exact expressions for the conserved charges and current profiles have been found for a spin-1/2 xxz model both in the free [68,73] and interacting [67] cases. Very recently, it was also shown that initial quantum correlations can suppress particle transport [74].…”
Section: Introductionmentioning
confidence: 99%